Effect of moxibustion on pain relief in patients with lower extremity arteriosclerosis obliterans of cold coagulation and blood stasis type (艾灸缓解下肢动脉硬化性闭塞症寒凝血瘀型患者疼痛的效果观察) - GUO Jing (郭晶); WANG Xiaodi (王晓娣); ZHI Hui (智慧); LIU Jinjing (刘津京) (Journal of International Translational Medicine Limited, 2022)
Objective To observe the effect of moxibustion on pain relief in patients with lower extremity arteriosclerosis obliterans (ASO)of cold coagulation and blood stasis type. Methods Totally 60 patients with lower extremity ASO of cold coagulation and blood stasis type were randomly divided into the control group and the observation group, with 30 cases in each group. Patients in both groups received routine care during the hospitalization, and those in the observation group were given moxibustion by Traditional Chinese Medicine (TCM) syndrome differentiation. The Visual Analogue Scale (VAS)was used to assess the degree of pain. Results The VAS score of the two groups decreased after nursing intervention, and VAS score in the observation group was lower than that in the control group (P＜0. 01). Conclusion The moxibustion by TCM syndrome differentiation is effective to relieve the pain of patients with lower extremity ASO of cold coagulation and blood stasis type. (目的 观察艾灸缓解下肢动脉硬化性闭塞症寒凝血瘀型患者疼痛的效果。方法 60例下肢动脉硬化性闭塞症寒凝血瘀型患者随机分为对照组和观察组, 各30例。对照组给予常规护理, 观察组在常规护理基础上增加中医护理干预, 根据中医辨证分型实施艾灸。采用视觉模拟评分(VAS)评估治疗前后患者疼痛程度。结果 干预后两组VAS评分均较干预前下降, 且观察组VAS评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 基于中医辨证分型实施艾灸, 能进一步缓解下肢动脉硬化性闭塞症寒凝血瘀型患者疼痛。)